Ajaran Kepanditaan Dalam Teks Lontar Wasista Tattwa - Ambarnuari, Mery; Hari Harsananda (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This article discusses the teachings of pandits contained in the lontar text Wasista Tattwa, a religious literary work that plays an important role in the religious and spiritual treasures of Hinduism in Bali. This study aims to explore and understand the values ​​of pandit contained in the text, as well as its relevance in the context of contemporary spiritual life. Using a qualitative approach through literature study and content analysis of the lontar text, this study found that Wasista Tattwa contains teachings on asceticism, self-control, physical and spiritual self-cleansing, and the virtues of life as a true pandit who sincerely serves the Dharma. This text emphasizes the importance of spiritual knowledge, ethics, and self-discipline as a foundation for someone who takes the path of pandit. The results of this study enrich the understanding of the heritage of Balinese religious literature and show that the teachings in Wasista Tattwa are still very relevant as ethical and spiritual guidelines for Hindus, especially prospective pandits.